La personne de confiance et les directives anticipées. Des dispositifs anti-trahison du patient en fin de vie ? - Camille Bourdaire-Mignot (Droit et Cultures, 2017)
The subject of the study is the appointed representative of the patient and the living wills, modified by the recent law of 2 February 2016. These measures were first designed to help medical personnel in their medical decisions. With the new law, the patient’s wishes recorded in their living wills have become legally binding on the practitioner. This evolution reveals the real purpose of these measures: to avoid the betrayal of the patient’s wishes. Nevertheless, neither of these measures can reduce the distance between patient’s wishes expressed formally in advance and consent of the end-of-life patient. For this reason, these measures would appear to be useless in avoiding the end-of-life patient betrayal. They have the potential to become the instruments of such a betrayal.